The importance of language skills within Europe - Cherednichenko, Galina (My University, 2015)
Learning a foreign language is an enriching experience. It encompasses much more than grammar and conversation exercises from textbooks. Not only is language a communication system, it is also a cultural code which transports complex information about cultural norms, values, traditions and rules of conduct. Foreign language competencies therefore enable deeper insights into other cultures and lifestyles.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; language skills; Europe; мовні навички; Європа; языковые навыки; Европа